2020
DOI: 10.1155/2020/2536272
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Infections in Neurological Surgery: The Changes of Circular RNA Expression and Their Possible Function Mechanism

Abstract: Background and Objective. Circular RNA (circRNA) often has high stability and has been widely studied as diagnostic markers in many diseases, including neurodegenerative disorders, diabetes, and various types of cancers. In this study, circRNA was evaluated as a diagnostic marker for central nervous system infection in neurological surgery. Methods. circRNA expression was analysed in six cerebrospinal fluid (CSF) samples from three patients of the infectious and noninfectious phases using an Arraystar Human ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, exosomes that exist almost in all body fluids have been reported to able to communicate CNS and peripheral systems by traversing the blood-brain barrier and transporting various biofunctional cargos. 25 Besides, evidence from other studies has revealed that circulating circRNAs were related to CNS diseases, 34,35 which indicated that circRNAs detected in the peripheral system can reflect the disease status in the CNS. Additionally, since the brain tissue is difficult to obtain in clinical practice, the stable circulating circRNAs provide a less invasive approach to observe and monitor the disease situation.…”
Section: Discussionmentioning
confidence: 99%
“…However, exosomes that exist almost in all body fluids have been reported to able to communicate CNS and peripheral systems by traversing the blood-brain barrier and transporting various biofunctional cargos. 25 Besides, evidence from other studies has revealed that circulating circRNAs were related to CNS diseases, 34,35 which indicated that circRNAs detected in the peripheral system can reflect the disease status in the CNS. Additionally, since the brain tissue is difficult to obtain in clinical practice, the stable circulating circRNAs provide a less invasive approach to observe and monitor the disease situation.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative patients A diagnostic marker for infection [53] 9 Oxidative Medicine and Cellular Longevity 5P leading to activation of fatty acid reductase 1 (Far1) with subsequent increase of the ROS leading to tissue damage [73].…”
Section: Cns Infectionmentioning
confidence: 99%
“…Functional analysis linked circRNA_008636 to FoxO3 and AMPK pathways, which mediate OxS. So, circRNA_008636 was suggested to be a mediator of infection-induced OxS and could be used among other circRNAs as a biomarker for early diagnosis of intracranial infection [ 53 ].…”
Section: Circrna and Oxs In The Nervous Systemmentioning
confidence: 99%